Effects of the dry season on two apple snails of the Amazon - Fonseca, Aldeiza Marques; Watanabe, Timóteo Tadashi [UNESP]; Hattori, Gustavo Yomar; Sant'Anna, Bruno Sampaio (My University, 2017)
The periodic variation in the water level of the Amazon basin is the mainfactor that determines the composition of the community of aquaticorganisms due to cyclical changes. As the dry season in the Amazonregion may vary according to environmental conditions that change fromyear to year, this study tested the hypothesis that long dry periods mayaffect populations of Pomacea considering survival rate, weight loss, growth and fattening of P. dolioides and P. diffusa after different periodsof dryness. Additionally, the maximum dryness resistance of both specieswas investigated. The mortality rate during the drying period was low and increased length of dry period for both the species. In the treatment with adry period of 70 days, the mortality rate was 2.22% for P. dolioides and8.89% for P. diffusa. In the treatment with a dry period of 130 days, itwas 8.89% for P. dolioides and 13.33% for P. diffusa. However, in thetreatment with a dry period of 190 days, it showed a higher mortality of11.11% for P. dolioides and 35.56% for P. diffusa. As for weight loss, there was a significant difference for the different periods of dryness (F =12.208; DF = 2; P < 0.000), between species (F = 5.619; DF = 1; P <0.018), with no influence of gender (F = 2.930; DF = 1; P > 0.088).Regarding growth, the different periods of dryness significantlyinfluenced the growth of the gastropods (F = 64.797; DF = 2; P < 0.000), between species (F = 28.676; DF = 1; P<0.000), with no influence ofgender (F = 0.305; DF = 1; P > 0.581). There was also differencebetween the of growth time and species (F = 12.578; DF = 2; P < 0.000).Fattening followed the same pattern, with significant influenceof the different periods of dryness (F = 150.120; DF = 2; P < 0.000), between species (F = 136.684; DF = 1; P < 0.000), with no influence ofgender (F = 0.148; DF = 1; P > 0.701). Pomacea dolioides was able tosurvive for 365 days while P. diffusa survived for 290 days in estivationexperiment. Both species had similar mortality and water loss rates. Therewas no difference between the resistance to dryness between the gendersof both species. The largest individuals of P. dolioides survived morethan smaller individuals, but for P. diffusa there was no difference. Pomacea dolioides survived longer than P. diffusa. These snails thoughadapted to overecome the long dry period. Longer dry periods affect thegrowth and fattening of individuals in the post-dry period, in addition toincreasing mortality rate imposing negative effects on gastropodpopulations.
Keywords: Dry period; Growth; Pomacea; Survival